Structural Analysis of Glaucoma Brain and its Association with Ocular Parameters (2020)
Purpose: To evaluate structural brain abnormalities in glaucoma patients using 3-Tesla magnetic resonance imaging and assess their correlation with associated structural and functional ocular findings. Patients and Methods: This cross-sectional prospective study included 30 glaucoma patients and 18 healthy volunteers. All participants underwent standard automated perimetry, spectral-domain optical coherence tomography, and 3.0-Tesla magnetic resonance imaging. Results: There was a significant difference between the surface area of the occipital pole in the left hemisphere of glaucoma patients (mean: 1253.9±149.3 mm2) and that of control subjects (mean: 1341.9±129.8 mm2), P=0.043. There was also a significant difference between the surface area of the occipital pole in the right hemisphere of glaucoma patients (mean: 1910.5±309.4 mm2) and that of control subjects (mean: 2089.1±164.2 mm2), P=0.029. There was no significant difference between the lingual, calcarine, superior frontal, and inferior frontal gyri of glaucoma patients and those of the control subjects (P>0.05 for all comparisons). The surface area of the occipital pole in the left hemisphere was significantly correlated with perimetry mean deviation values, visual acuity, age, and retinal nerve fiber layer thickness (P=0.001, P<0.001, P=0.010, P=0.006, respectively). The surface area of the occipital pole in the right hemisphere was significantly correlated with perimetry mean deviation values, visual field indices, visual acuity, age, and retinal nerve fiber layer thickness (P<0.001, P=0.007, P<0.001, P=0.046, P<0.001, respectively). Conclusions: Glaucoma patients presented a decreased occipital pole surface area in both hemispheres that independently correlated with functional and structural ocular parameters. Copyright © 2020 Wolters Kluwer Health, Inc.